The influence of aspiration on the fundamental frequency in Danish: Some preliminary observations - Reinholt Petersen, Niels (Annual Report of the Institute of Phonetics University of Copenhagen, 1978)
Some preliminary observations are reported which seem to indicate that the fundamental frequency of a stressed vowel is higher after an aspirated than after an unaspirated stop consonant, and that the difference is not restricted to the beginning of the vowel but is also found at the middle and frequently all through the vowel.